Candidate codes in the gustatory system of caterpillars (The Rockefeller University Press, 1982)
Larvae of tobacco hornworms offer unique opportunities to relate the electrophysiological output of identified chemosensory neurons to specific behavioral responses. Larvae can discriminate among three preferred plants with only eight functioning gustatory receptors. They can be induced to prefer any one of the plants, and these preferences can be reversed. All eight neurons respond to each plant sap. Two fire too infrequently to permit detailed analysis. Analyses of the remaining six show that all electrophysiological responses consist of phasic and tonic components. Only the "salt best" cell fires during the phasic period. Temporal analysis of the spike train during this period shows that tomato and tobacco could be distinguished from Jerusalem cherry but not from each other by a rate code. Measurements of behavioral response times together with the nonspecificity of this with respect of food plants, unacceptable plants, and sodium chloride eliminate a phasic period rate code as a probable mechanism for complex discrimination. Events occurring in the tonic period, when all cells are firing, suggest a major role for this period. Analyses of variance in the interval frequencies of the large and medium spikes suggest that a variance code could allow discrimination among the three plants as long as both cells were firing at the same time. Evidence has been found for temporal patterning in the tonic response of the "salt best" cell to Jerusalem cherry but is absent elsewhere. The most likely basis for coding the difference between each of the three plants is across- fiber patterning in which the relative rates of firing and the variances of all the sensory neurons in the tonic phase are critical.